The relationship of pension funds with financial markets development - Miloš Grujić (Journal of Contemporary Economic and Business Issues, 2019)
This paper empirically explores the impact of pension funds on market development. The goal of the paper is to link the credit rating of a country and the development of the financial market. At the same time, we will make a link between the structure and size of pension funds and the development of financial markets across countries. The development of the market is expressed with the help of the FD index, the size of pension funds as a size related to GDP, the structure of pension funds, as a participation of shares or bonds in relation to total assets and in relation to GDP, and the size of funds is expressed in relation to the GDP of the country. The research question states: "Does the size and structure of pension funds influence the development of the financial market in the country"? The methodology applied consists of qualitative research techniques, such as analysis, comparative analysis, correlation between the two observed variables and synthesis. Thus, this research was provided during the summer of 2019. The selected group of countries was based on two criteria based on data from 2018: OECD countries and the others. Methodology used is based on some previous research related to the financial development index. The research refers to looking for answers to the question of what is the dependence like between the structure and size of pension funds on one hand, and the development of the financial market on the other. The contribution of the paper is reflected in the explanation of the possibilities that pension funds with their structure and size offer to the development of the financial market in the country. The result shows that pension funds can provide a significant support for financing the development of the country, local communities, but that between certain phenomena, such as the size and structure of funds and the size of the economy and the development of the financial market, there is only a poor determination. This paper has intentions to offer a special strategy for creating a portfolio and it is an initial step towards further analysis and directions on the portfolio management.
Keywords: D53; E44; 330; pension funds; investment funds; development of the financial market